THU0165 Risk of herpes zoster in patients with rheumatoid arthritis in the biologics era based on the iorra cohort. (15th June 2017) - Yamaguchi, R; Nakajima, A; Inoue, E; Ochiai, M; Shimizu, Y; Sugimoto, N; Tanaka, E; Ikari, K; Taniguchi, A; Yamanaka, H
Abstract : Background: A high incidence of herpes zoster (HZ) in patients with rheumatoid arthritis (RA) has been reported (1). According to our previous report on the incidence of HZ in Japanese patients with RA enrolled in the IORRA (Institute of Rheumatology, Rheumatoid Arthritis) cohort from 2005 to 2010, the standardized incidence rate (SIR) of HZ per 1, 000 patient-years was 9.1 (95% confidence intervals [95% CIs]: 6.2–12.9) (2). In that study, 3.0% of patients used biologics at baseline. Subsequently, the use of biologics has increased, and many new potent disease-modifying antirheumatic drugs (DMARDs) have been introduced. The treatment strategy for RA has progressed in recent years; thus, it is important to investigate whether there is a change in the HZ incidence rate and the risk factors for HZ with the expanded use of biologics. Objectives: To elucidate the incidence of HZ and risk factors for HZ in RA patients in the IORRA cohort. Methods: The IORRA cohort is a large, single institute-based, observational cohort of RA patients established at the Institute of Rheumatology, Tokyo Women's Medical University, in 2000. Among patients with RA enrolled in the IORRA surveys from 2010 to 2015, the incidence of HZ was extracted based on patients' self-report and confirmed by the medical records. The SIR with 95% CIs was calculated and risk factors for HZ were analyzed using a Cox regression analysis. Results: For 7, 815 patients with RA (female, 84.7%) who were analyzed, the median [interquartile range (IQR)] age was 61.0 [49.7–68.9] years, and disease duration was 10 [4–18] years. Baseline drugs (median dose [IQR]) included prednisolone (PSL, 4 [2–5] mg/day) in 36.8%, methotrexate (MTX, 8 [6–10] mg/week) in 70.4%, and biologics in 14.7% of patients. Among 7, 815 patients with 25, 863 patient-years of observation (male, 3, 828; female, 22, 035), 340 HZ events were confirmed in 309 patients (21 patients had multiple events). The SIR per 1, 000 patient-years was 8.5 (95% CI: 6.9–10.5) in total, 6.0 (95% CI: 3.7–9.2) in males, and 11.0 (95% CI: 8.7–13.7) in females. The following hazard ratios (HR) were found: unit increase of age, 1.14 (95% CI: 1.03–1.26, p<0.05); J-HAQ score 0.5–1.5 (reference J-HAQ score =0), 1.51 (95% CI: 1.09–2.10, p<0.05); MTX use, 1.58 (95% CI: 1.06–2.36, p<0.05); and biologics use, 1.88 (95% CI: 1.44–2.47, p<0.01). PSL use was not a risk factor (PSL dose <5 mg/day: HR 1.17 [95% CI: 0.91–1.51, p=0.22]; PSL dose ≧ 5 mg/day: HR 1.17 [95% CI: 0.72–1.91, p=0.52]; the reference PSL dose =0 mg/day). Conclusions: The drugs that were a risk factor for HZ were PSL and MTX in our previous study when the use of biologics was not prevalent. In this study, the drugs that were a risk factor for HZ were MTX and biologics, but not PSL in the era when the use of biologics became frequent. References: Wolfe F et al. Rheumatology (Oxford). 2006;45:1370. Nakajima A et al. Mod Rheumatol 2015;25:558. Disclosure of Interest: R. Yamaguchi: None declared, A. Nakajima Consultant for: Bristol-Meyers, Mitsubishi Tanabe Pharma, Nippon Kayaku Co. Ltd., Novartis Pharma, Pfizer, Siemens Healthcare Diagnostics K.K. and Takeda Pharmaceutical Company., Speakers bureau: Bristol-Meyers, Mitsubishi Tanabe Pharma, Nippon Kayaku Co. Ltd., Novartis Pharma, Pfizer, Siemens Healthcare Diagnostics K.K. and Takeda Pharmaceutical Company., E. Inoue: None declared, M. Ochiai: None declared, Y. Shimizu: None declared, N. Sugimoto Speakers bureau: Takeda Pharmaceutical and Bristol Myers Squibb., E. Tanaka Consultant for: Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Pfizer, Takeda Pharmaceutical, and Ayumi Pharmaceutical., K. Ikari Grant/research support from: Astellas, UCB, Bristol-Meyers, Pfizer, Eisai, Tanabe-Mitsubishi, Chugai, AbbVie, Janssen Pharmaceutical, Otsuka, Kaken, Asahi-Kasei, Hisamitsu and Takeda., Speakers bureau: Astellas, UCB, Bristol-Meyers, Pfizer, Eisai, Tanabe-Mitsubishi, Chugai, AbbVie, Janssen Pharmaceutical, Otsuka, Kaken, Asahi-Kasei, Hisamitsu and Takeda., A. Taniguchi Grant/research support from: AbbVie, Eisai, Takeda, Tanabe-Mitsubishi, Teijin Pharma, Pfizer., Speakers bureau: AbbVie, Eisai, Takeda, Tanabe-Mitsubishi, Teijin Pharma, Pfizer., H. Yamanaka Grant/research support from: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers., Consultant for: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers., Speakers bureau: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers.